Seroprevalence of Infectious Bronchitis Virus in Broiler and Layer Farms of Central Ethiopia. (2nd March 2022) - Shiferaw, Jirata; Dego, Tamiru; Tefera, Misgana; Tamiru, Yobsan
Abstract : Background . Infectious bronchitis virus (IBV) is a highly contagious viral disease of chicken typically affecting the reproductive and respiratory tract and results in possible economic causes from its serious infectious and transmission characteristics. Methods . A cross-sectional study was carried on serum samples of chickens selected from six (two commercial and four small holder) farms and two types of production (broiler and layer) to detect seroprevalence of IBV and its associated risk factors in Bishoftu and Holeta areas of central Ethiopia from June 2021 to September 2021. A total of 354 blood samples were collected and subjected to indirect ELISA test by IBV antibody test kit ((ProFLOK IBV), from ProFLOK Laboratories Inc., (USA)) to detect specific antibodies against IBV. Results . Overall, 97.46% seroprevalence was identified. From 230 and 124 samples collected from commercial and smallholder poultry farms, 226 (98.26%) and 119 (95.98%) positive results were obtained, respectively. Among the production types of chickens, high seroprevalence (99.31%) was found in layer poultry, and lower seroprevalence (96.17%) was found in the case of broiler chicken. Significant association was observed among different associated risk factors particularly age, sex, breed, and production types of chickens. From the tested chickens, all age groups, species, and farm types have high seroprevalence of IBV. The prevalence of IBV was highly significant (p ≤ 0.01 ) in the study site. The risk factors indicated could have increased infection prevalence, pathogens' economic impact, and disease occurrence. Conclusion . IBD is complicating factor affecting poultry production systems in the area. Vaccine and biosecurity measures are recommended for the control of IBV. Furtherly, identification and characterization (by using RT-PCR) of persistent serotype of IBV circulating in the field are recommended.